Kon vino i esperansa todo se alkansa: Cuisine and Cultural Memory in the Sephardic Jewish Diaspora. - Gardner, Sara M. (Tufts Archival Research Center, 2016)
Following the arc of a traditional Sephardic meal, this thesis explores through five access points Sephardic Jewish culinary heritage and cultural identity in the diaspora. This thesis is related to, but different from, the Summer Scholars project under the same name that can also be found in the digital archive.